Hearing Outcome after Ossiculoplasty with Teflon Ossicular Replacement Prosthesis in Modified Canal Wall Up Mastoidectomy - Sohel, Shah; Hossain, Delwar; Talukder, Sabyasachi; Tanjil Ul Alam, Sheikh; Nawshin, Tamanna; Hamid, Abdul; Islam, Nazrul (Bangladesh Journal of Otorhinolaryngology, 2024)
Background: Cholesteatoma commonly leads to damage of ossicular chain. Modified canal all up mastoidectomy is one of the commonly performed procedure for cholesteatoma worldwide. Ossiculoplasty means the operation performed to reconstruct the ossicular chain. Aim: To evaluate the hearing outcome after ossiculoplasty with teflon ossicular replacement prosthesis in modified canal wall up mastoidectomy. Methods: A prospective observational study was conducted at the Dept. of Otolaryngology-Head & Neck Surgery, Bangabandhu Sheikh Mujib Medical University, Shahbagh, Dhaka from March 2018 to June 2020. Total 34 patients with cholesteatoma underwent modified canal wall up mastoidectomy and ossiculoplasty with teflon TORP or PORP were included in this study. All patients were followed up post-operatively upto 6 months with PTA. Results: Hearing improvement was better in ossiculoplasty with PORP. Successful results (ABG closure to within 20dB) were obtained in 35.29% & 70.58% cases in TORP & PORP group respectively after six month post-operatively. Conclusion: Ossiculoplasty with teflon ossicular replacement prosthesis gives satisfactory hearing gain. Bangladesh J Otorhinolaryngology 2024; 30(1): 24-33